Penukilan ilmu baharu melalui sejarah lisan - Saad, Siti Roudhah Mohamad; Mohamad, Radia Banu Jan; Jaafar, Cik Ramlah Che; Jan, Noor Azlinda Wan (Persatuan Pustakawan Malaysia, 2012)
Oral history is an important method used to record events that a person has gone through. Historical records of an event can be completed through oral history since part of the information still resides in a person’s memory.Interview is one method that is used in oral history to collect information from an individual. The oral history interview scope covers all levels within a society in order to gain a new perspective on historical events.In 1982, Universiti Sains Malaysia formed the Committee on Oral History in order to gather information about the Japanese occupation in the northern areas of peninsular Malaysia.The committee members had historians as well a librarian for the University’s library. The librarian is responsible for the recordings and the transcriptions.The historical compilations that are kept in the Library can generate new knowledge. Therefore there should be a structured promotion plan. Technological developments can aid in the dissemination of the collection to a wider audience.This paper will explain the importance of oral history, background of the collection held in the USM Library and efforts undertaken to promote this information source as an important material for research on history in the near future.